Designing large arrays of tidal turbines: A synthesis and review. (January 2015) - Vennell, Ross; Funke, Simon W.; Draper, Scott; Stevens, Craig; Divett, Tim
Abstract: Much of the global tidal current energy resource lies in the accelerated flows along narrow channels. These channels have the potential to produce 10–1000 s of MW of electricity. However, realizing 100 MW of a channel׳s potential is much more complex than installing 100 1-MW turbines because large scale power extraction reduces tidal currents throughout the channel, changing the resource. This synthesis and review gives an overview of the issues and compromises in designing the layout of the large tidal turbine arrays required to realize this potential. The paper focuses on macro- and micro-design of arrays. Macro-design relates to the total number of turbines and their gross arrangement into rows, while micro-design adjusts the relative positions of the turbines within a grid and the spacing between rows. Interdependent macro-design compromises balance the total number of turbines, array power output, the power output of each turbine, the loads the turbines experience, turbine construction costs, maintaining navigability along the channel and any environmental impacts due to flow reduction. A strong emphasis is placed on providing physical insights about how "channel-scale dynamics" and the "duct-effect" impact on the compromises in array design. This work is relevant to the design of any "large" array which blocks more than 2–5% of a channel׳s cross-section, be it 2 turbines in a small channel or 100 turbines in a large channel.